Willingness to protest over resource extraction in Latin America. Issue 2 (April 2020) - Arce, Moises; Polizzi, Marc S.; Reeder, Bryce W.
Highlights: Predicts willingness to protest over resource extraction. Socially engaged individuals are more willing to protest. Individuals living in countries with stronger governance capabilities are more willing to protest over resource extraction. Abstract: Protests over resource extraction have increased in Latin America in recent years. However, significant variation exists in the region in terms of citizen's willingness to protest against resource extraction. We argue that this variation is based on the interaction of factors at both the individual and state levels. Individual-level characteristics, such as social engagement, influence the likelihood of protest activity. State-level characteristics, such as the quality of governance, also present opportunities for engaged individuals to challenge resource extraction. Following political mediation theory, we argue that collective action strategies are likely to be more productive in some political contexts than in others. Thus socially-engaged citizens in high-quality governance environments are more willing to participate in protests over resource extraction vis-a-vis their counterparts in low-quality governance settings. We utilize survey data and state-level governance data across Latin America to determine why some individuals are willing to demonstrate against resource extraction while others are not.